Hyphantria cunea (Drury, 1773) new for the Maltese Islands (Lepidoptera: Erebidae, Arctiinae, Arctiini) - Anthony Seguna; Aldo Catania; Paul Sammut; John J. Borg (SHILAP)
The genus Hyphantria Harris, 1841 and the species Hyphantria cunea (Drury, 1773) are recorded for the first time from the Maltese Islands. Notes on the distribution, habits of the adult and larval host plant are included. A Maltese name is proposed for this new record.